Arab Descendant Identity in Media: A Discourse Analysis of Suara al-Irsyad - Madihah, Madihah; Sarbini, Ahmad; Muhyiddin, Asep; Wibisono, M. Yusuf (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This study examines the representation of Arab descendants’ identity in Indonesia through the community-based media Suara Al-Irsyad (MSA). Media play a crucial role in shaping and preserving community identity, particularly within diasporic groups facing globalization and social transformation. This research aims to explore how MSA contributes to maintaining Arab descendants’ cultural identity and the strategies employed to remain relevant in the digital era. Employing a qualitative approach with a descriptive-analytical method, data were collected through direct observation, in-depth interviews with MSA administrators, and document analysis of its publications. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that MSA functions not only as an information platform but also as a medium for cultural preservation. Beyond reporting news and Islamic education, MSA constructs an inclusive narrative that highlights the contributions of Arab descendants to national development. To address digital challenges, MSA has implemented modernization strategies by leveraging social media platforms to engage younger audiences. Despite declining interest in community-based media and increasing competition from mainstream platforms, MSA sustains its relevance by balancing traditional values with technological innovation. This research contributes to media and identity studies by demonstrating the critical role of community media in constructing minority group representations in the public sphere. It enriches the discourse on diaspora identity dynamics in the context of media, particularly in navigating globalization and social change. Moreover, the study provides practical implications for media practitioners, scholars, and policymakers in formulating sustainable strategies for ethnic-based media in the digital era.